2016
DOI: 10.21071/az.v65i250.483
|View full text |Cite
|
Sign up to set email alerts
|

Análise de crescimento da gliricídia submetida a diferentes manejos de corte

Abstract: Objetivou-se avaliar as respostas de crescimento da Gliricídia sepium submetida a diferentes manejos de corte. O delineamento utilizado foi o de blocos ao acaso no esquema de parcelas subdivididas, em que a frequência de corte (45, 60, 75 e 90 dias) compreendeu a parcela principal e a altura de resíduo (30, 60 e 90 cm), a subparcela. A análise do crescimento foi obtida por meio da determinação da área foliar específica, índice de área foliar, taxa de crescimento relativo, taxa assimilatória líquida e taxa de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
3
0
4
Order By: Relevance
“…Dry matter (%) 16 The mold and yeast (MY) count with 7 days of opening after ensiling is similar, averaging 7.47. With 90 days of ensiling, the MY number is reduced to 5.39, 4.93, 4.96, 5.64, and 4.56 for the treatments with 0, 25,50,75, and 100% addition of gliricidia in cactus pear silage (Fig.…”
Section: Cactus Pear Gliricidiamentioning
confidence: 96%
See 2 more Smart Citations
“…Dry matter (%) 16 The mold and yeast (MY) count with 7 days of opening after ensiling is similar, averaging 7.47. With 90 days of ensiling, the MY number is reduced to 5.39, 4.93, 4.96, 5.64, and 4.56 for the treatments with 0, 25,50,75, and 100% addition of gliricidia in cactus pear silage (Fig.…”
Section: Cactus Pear Gliricidiamentioning
confidence: 96%
“…It is known that the main problem associated with legume silage is the high protein content and low soluble carbohydrate content 15 . Among the legumes, gliricidia is highlighted, emerging as an alternative feed for the herds of the semiarid region, with high production of dry matter, reaching 10.7 t/ha in the rainy season and 9.7 t/ha in the dry season, besides desirable nutritional characteristics, such as 30% dry matter and from 20 to 30% crude protein [16][17][18] . However, in the particular case of the gliricidia, some authors have demonstrated that the final pH values of their silages are always high 19,20 .The combination of cactus pear with gliricidia would be an alternative to achieve the desired final pH, by predominating the lactic fermentation to the detriment of the alcoholic fermentation, besides improving the silage nutritional characteristics, since the cactus pear shows high content of water-soluble carbohydrates, which are extremely important in the fermentation process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A Gliricidia sepium (Jacq.) Steud., pertence a família Fabaceae, conhecida como gliricídia, é uma leguminosa arbórea e resistente a seca, que vem sendo considerada uma forrageira de interesse comercial e econômico no Semiárido nordestino, devido suas características de uso múltiplo (Edvan et al, 2016;Oliveira et al 2018b).…”
Section: Gliricidia Sepium (Jacq) Steud)unclassified
“…Segundo Matos et al (2005), trata-se de uma forrageira pouco exigente no tocante a fertilidade do solo, possuindo melhor desenvolvimento em regiões com clima quente, onde os meses mais frios apresentam temperatura mínima de 14 ºC a 20 ºC e nos meses mais quentes de 34 ºC a 41 ºC. A leguminosa tem capacidade de rebrota, suportando cortes periódicos (até três cortes ao ano) e produzindo volumoso de qualidade em condições de baixa disponibilidade hídrica (Marin, Menezes & Salcedo, 2007;Paulino, Barroso, Lamônica, Costa & Carneiro, 2011;Edvan et al, 2016).…”
Section: Gliricidia Sepium (Jacq) Steud)unclassified